Measuring Visitor Experiences: Creating and Testing the Tourism Autobiographical Memory Scale. (April 2019) - Jorgenson, Jake; Nickerson, Norma; Dalenberg, Douglas; Angle, Justin; Metcalf, Elizabeth; Freimund, Wayne
The purpose of this study was to test the validity of the new Tourism Autobiographical Memory Scale (TAMS) that measures visitor experience through personal memory. The TAMS uses the autobiographical memory framework to represent the degree to which a travel experience was impactful to a traveler's life. Visitors were asked to recall a memory from their visit to a national park and rate the memory of the experience based on its impact and frequency of rehearsal on a 7-point scale. Using exploratory factor analysis and reliability testing, two distinct factors emerged. Results identified a reliable measure of a memory's impact and frequency of rehearsal of tourists. The TAMS provides researchers a new scale to gather information about the impact of a visitor experience from the direct source—personal memories. Destination managers who understand the impact they can have on a traveler will be able to manage and market to those types of experiences.